PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PNS PADA PUSTAKA WILAYAH PROVINSI RIAU - Wicak, Sana Wicak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
his research aims to determine the influence of work discipline and supervision on the performance of civil servant employees in the Regional Library of Riau Province. This research method is quantitative descriptive, which means the research is explained in statistical form or in the form of numbers. The population in this study was 100 civil servant employees at the Regional Library of Riau Province. The results of this research show (1) Work discipline influences performance (2) Supervision influences performance (3) Work discipline and supervision influences performance Keywords: Work Discipline, Supervision and Performance